2016
DOI: 10.1101/gad.289553.116
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ARGONAUTE4–DNA interactions in RNA-directed DNA methylation in plants

Abstract: RNA polymerase V (Pol V) long noncoding RNAs (lncRNAs) have been proposed to guide ARGONAUTE4 (AGO4) to chromatin in RNA-directed DNA methylation (RdDM) in plants. Here, we provide evidence, based on laser UV-assisted zero-length cross-linking, for functionally relevant AGO4-DNA interaction at RdDM targets. We further demonstrate that Pol V lncRNAs or the act of their transcription are required to lock Pol V holoenzyme into a stable DNA-bound state that allows AGO4 recruitment via redundant glycine-tryptophan/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 31 publications
2
86
0
3
Order By: Relevance
“…However, ago4 mutants exhibit a much more severe loss of CHH methylation (Stroud et al, 2013), clustering with the nrpe1-11 , full CTD, or DeCL subdomain deletions (Figure 4A). This finding is consistent with evidence that AGO4 recruitment entails interactions with Pol V transcripts and SPT5L, not just the NRPE1 CTD (El-Shami et al, 2007; Lahmy et al, 2016; Pontier et al, 2012; Wierzbicki et al, 2009). …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, ago4 mutants exhibit a much more severe loss of CHH methylation (Stroud et al, 2013), clustering with the nrpe1-11 , full CTD, or DeCL subdomain deletions (Figure 4A). This finding is consistent with evidence that AGO4 recruitment entails interactions with Pol V transcripts and SPT5L, not just the NRPE1 CTD (El-Shami et al, 2007; Lahmy et al, 2016; Pontier et al, 2012; Wierzbicki et al, 2009). …”
Section: Resultssupporting
confidence: 90%
“…Interestingly, methylated loci dependent on the linker, 17aa repeat, or QS subdomains are similarly dependent on proteins that interact with Pol V or its transcripts, including SPT5L, the IDP complex (IDN2, IDNL1, IDNL2), AGO6, or RRP6L1, implicating these CTD subdomains in diverse co-transcriptional steps of the RdDM process. In support of the possibility that the CTD subdomains may serve multiple roles, a study was published while this manuscript was in preparation that demonstrated restoring the 17 aa repeats into the NRPE1ΔSD construct rescues DNA methylation at affected loci, even upon changing the WG motifs to AG motifs, suggesting an unknown function for the repeats other than AGO binding (Lahmy et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…These results indicate strong conservation of components of GI protein‐interaction partners across different plant species. We also identified additional interesting candidates, such as an essential light signal receptor PHYTOCHROME C ( PHYC ; Woods, Ream, Minevich, Hobert, & Amasino, ), an RNA‐directed DNA methylation pathway gene ARGONAUTE 4 ( AGO4 ; Lahmy et al, ), a cold response and root hair regulator GLYCINE RICH PROTEIN 8 ( GRP8 ; Carpenter, Kreps, & Simon, ; Foley et al, ), and a cell wall modification gene EXPANSIN 13 ( EXP13 ; Lee, Choi, & Kende, ), with strong coexpression patterns with PhGI under SD, LD, or both conditions (Table S11). The functional diversity of these coexpressed genes might help to understand the pleiotropic roles of GI in the external coincidence model.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure, in combination with immunochemical techniques (laser X‐ChIP‐qPCR), was used to detect the presence of specific proteins on DNA sequences of interest in whole cells. These included RNA pol II and the androgen receptor (AR) , as well as RNA pol V and AGO4 in nuclei isolated from plant cells . The above examples demonstrate the utility of the UV laser cross‐linking for gaining relevant structural and conformational information that cannot be obtained using either the conventional UV irradiation or formaldehyde cross‐linking techniques.…”
Section: Main Reactions Of Base Radical Cations In Isolated Dnamentioning
confidence: 99%